Factors affecting contraceptive prevalence rate in Samarahan district, Sarawak, Malaysia - Diana, Anak Jawa. (Universiti Malaysia Sarawak (UNIMAS), 2013)
The contraceptive prevalence rate (CPR) is an important indicator in achieving the Millenium Developement Goal (MDG) by 2015. Despite all the efforts to improve the contraceptive prevalence rate (CPR) in Malaysia after 1984, the CPR has levelled off at the range of 52% since then. In Sarawak, CPR increase slightly from 50.1% in 1989 to 53.0% in 2004. this was a cross-sectional study to determine the factors affecting the contraceptive prevalence rate.